ANALYSIS OF RISK FACTORS AFFECTING THE INCIDENCE OF HYPERTENSION IN THE WORKING AREA OF THE TALANG RATU PALEMBANG HEALTH CENTER - Muhammad Baharul Iman; Akhmad Dwi Priyatno; Muhammad Prima Cakra Randana; Arie Wahyudi; R.A. Lisna Dwi Rahma (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Hypertension is one of the non-communicable diseases whose prevalence continues to rise both globally and nationally, including in the working area of Talang Ratu Public Health Center, Palembang City. The risk factors for hypertension are classified into modifiable and non-modifiable factors. This study is an observational analytic research with a cross-sectional design. The sample consisted of 241 respondents selected using consecutive sampling from patients visiting the Talang Ratu Health Center in February 2025. Data were collected through interviews using questionnaires and direct measurement tools. Analysis was conducted using univariate, bivariate (Chi-square), and multivariate (multiple logistic regression) methods. The results showed that variables significantly associated with hypertension were age (p = 0.000), obesity (p = 0.001), physical activity (p = 0.005), fast food consumption (p = 0.003), stress (p = 0.010), and family history of hypertension (p = 0.000). Non-significant variables included gender (p = 0.748) and smoking habits (p = 0.576). The most dominant factor was age (OR = 6.912). It is concluded that age is the main risk factor for hypertension. Promotive and preventive efforts targeting modifiable risk factors should focus on high-risk age groups.